2004
DOI: 10.1007/s00406-004-0516-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention deficit–/hyperactivity disorder (ADHD) and comorbid disorders in young male prison inmates*

Abstract: The prevalence of DAA/HCD or ADHD in young adult prison inmates is significantly elevated when compared to nondelinquent controls. Generally the population of young adult male prison inmates exhibits a considerable psychiatric morbidity. Of the total sample, 64% suffered from at least 2 disorders. Only 8.5% had no psychiatric diagnoses. This indicates the urgent need for more psychiatric expertise in young offender facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
159
1
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(193 citation statements)
references
References 41 publications
17
159
1
16
Order By: Relevance
“…Research conducted within prison settings has found significantly increased prevalence rates of ADHD among inmates when compared to non-delinquent controls (Ginsberg et al 2010;Rösler et al 2004). Moreover, ADHD symptomatology has been linked to critical incidents within prison settings (Young et al 2009), with symptomatic prisoners likely to engage in a greater frequency and more severe incidents.…”
Section: Prevalence Of Adult Adhd In An All Female Prison Unitmentioning
confidence: 99%
“…Research conducted within prison settings has found significantly increased prevalence rates of ADHD among inmates when compared to non-delinquent controls (Ginsberg et al 2010;Rösler et al 2004). Moreover, ADHD symptomatology has been linked to critical incidents within prison settings (Young et al 2009), with symptomatic prisoners likely to engage in a greater frequency and more severe incidents.…”
Section: Prevalence Of Adult Adhd In An All Female Prison Unitmentioning
confidence: 99%
“…1 The disorder is characterised by behavioural and attention difficulties, which can lead to secondary problems such as drug addiction and delinquency in adults. 2 Sleep deficits are a prominent characteristic of the disorder, with up to 83% of adult with ADHD reporting problems with sleep. 3 Actigraphy and polysomnography studies of sleep disturbance in ADHD have demonstrated significant association of sleep disturbance with both childhood and adult ADHD, including delayed sleep onset and difficulties in awakening, increased nocturnal activity, reduced sleep efficiency and reduced percentage of Rapid Eye Movement (REM) sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Des études de cohorte de naissances ont également montré que le TDAH était lié à une trajectoire de comportements agressifs qui persistait de l'enfance à l'âge adulte (Odgers et al, 2007) et à un risque plus élevé de décès par suicide à l'âge adulte (Barbaresi et al, 2013). Dans les milieux carcéraux, la prévalence du TDAH se situe générale-ment autour de 10 à 20 % (Cahill et al, 2012 ;Colins et al, 2010 ;Fazel, Doll et Langstrom, 2008 ;Retz et Rösler, 2010 ;Usher, Stewart et Wilton, 2013 ;Westmoreland et al, 2010), mais des taux plus élevés ont aussi été rapportés (Einarsson, Sigurdsson, Gudjonsson, Newton et Bragason, 2009 ;Ginsberg, Hirvikoski et Lindefors, 2010 ;Rösler et al, 2004). Plusieurs études démontrent que le TDAH se présente le plus souvent en comorbidité avec d'autres troubles, en particulier les troubles de l'humeur, les troubles anxieux, les troubles psychotiques, le trouble de la personnalité limite, le trouble de la personnalité antisociale et les troubles liés à l'utilisation de substances (alcool et drogue) (Einarsson et al, 2009 ;Rösler et al, 2004 ;Spencer et al, 2007 ;Westmoreland et al, 2010).…”
Section: Mots Clés • Prison Tentative De Suicide Tdah Santé Mentaleunclassified
“…Dans les milieux carcéraux, la prévalence du TDAH se situe générale-ment autour de 10 à 20 % (Cahill et al, 2012 ;Colins et al, 2010 ;Fazel, Doll et Langstrom, 2008 ;Retz et Rösler, 2010 ;Usher, Stewart et Wilton, 2013 ;Westmoreland et al, 2010), mais des taux plus élevés ont aussi été rapportés (Einarsson, Sigurdsson, Gudjonsson, Newton et Bragason, 2009 ;Ginsberg, Hirvikoski et Lindefors, 2010 ;Rösler et al, 2004). Plusieurs études démontrent que le TDAH se présente le plus souvent en comorbidité avec d'autres troubles, en particulier les troubles de l'humeur, les troubles anxieux, les troubles psychotiques, le trouble de la personnalité limite, le trouble de la personnalité antisociale et les troubles liés à l'utilisation de substances (alcool et drogue) (Einarsson et al, 2009 ;Rösler et al, 2004 ;Spencer et al, 2007 ;Westmoreland et al, 2010). Le TDAH, en lien avec ses comorbidités, est associé aux gestes agressifs et aux inconduites en établissement (Usher et al, 2013 ;Young et Thome, 2011), à la persistance des symptômes du TDAH (Ginsberg et al, 2010 ;Vermeiren, 2003) ainsi qu'à un risque plus élevé de décès par suicide (Westmoreland et al, 2010).…”
Section: Mots Clés • Prison Tentative De Suicide Tdah Santé Mentaleunclassified